Evaluation of Business Continuity Plan Maturity Level Using Business Continuity Maturity Model (International Journal of Innovative Computing, 2018)
Business Continuity Plan (BCP) plays an important part in ensuring the business continuity of an organization in the event of major disruptions. In order to ensure the continuity of their critical business functions and critical services during and after a disaster, healthcare organizations such as hospitals, clinics, hospices and others can implement BCP models in their respective organizations to ensure their business continuity during and after disruptive incidents. After implementing BCP models in their respective healthcare organizations how can they ensure the BCP models will be useful and effective when disasters strike. Therefore, maturity models can help to analyze the maturity level of the BCP model. The higher the level of maturity of the BCP models, the higher the probability of effectiveness and usefulness of the BCP models. The goal of this research is to determine how compliance the existing maturity models for business continuity towards ISO 22301 standard and to map existing BCP healthcare model with business continuity maturity model.